Social capital of community forest management on Nusapati Village, Mempawah District, West Kalimantan, Indonesia - EMI ROSLINDA; WIWIK EKYASTUTI; SITI MASITOH KARTIKAWATI (Society for Indonesian Biodiversity, 2017)
Roslinda E, Ekyastuti E, Kartikawati SM. 2017. Social capital of community forest management on Nusapati Village, Mempawah District, West Kalimantan, Indonesia. Biodiversitas 18: 548-554. Community forest management has been recognized over the past two decades as a potential approach for achieving forest sustainability. In Indonesia, community forestry was developed by a government program with limited funds. Community forestry in Nusapati village was one of many successful community forest programs. The aim of this study was to explore how social capital developed in Nusapati community relating to community forest management was developed and reinforced. The survey method was used in this research. Data collection was undertaken through general field observation, key informant interviews, and semi-structured respondent interviews with a questionnaire. The results show that social capital was significantly correlated to trust, social norms, and social networks in the development of community forestry. This study concludes that social capital of Nusapati community is strong, which suggest that government intervention through development programs should take social capital into consideration.